2012
DOI: 10.3176/oil.2012.4.06
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-Ct Study of Changes in the Internal Structure of Daqing and Yan’an Oil Shales at High Temperatures

Abstract: A high-precision computed tomography (CT) experimental analysis system was used to perform a non-invasive CT scanning of oil shales (OS) from Daqing and Yan'an counties, Heilongjiang and Shanxi provinces, respectively, both northeastern China, in order to study changes in their internal structure at high temperatures. The formation and pattern of pores and fractures with increasing temperature was examined. Professional CT analysis software was used to statistically calculate porosities. The experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 5 publications
(5 reference statements)
0
24
0
Order By: Relevance
“…Using X-ray micro tomography, Tiwari et al [10] obtained a lower porosity of 21% at 500°C. Using macro-CT analysis, Zhao et al [17] also reported that the porosities of Daqing and Yan'an oil shales pyrolyzed at 600°C were 31.61% and 8.86%, respectively. However, our results are almost consistent with those obtained by Sun et al [20] with pycnometry testing.…”
Section: Permeability Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Using X-ray micro tomography, Tiwari et al [10] obtained a lower porosity of 21% at 500°C. Using macro-CT analysis, Zhao et al [17] also reported that the porosities of Daqing and Yan'an oil shales pyrolyzed at 600°C were 31.61% and 8.86%, respectively. However, our results are almost consistent with those obtained by Sun et al [20] with pycnometry testing.…”
Section: Permeability Analysismentioning
confidence: 96%
“…Recently, Kang et al [9] studied the thermal cracking and the corresponding permeability coefficient which is parallel to the shale bedding plane [abbreviated as permeability (PABP)] of oil shale during pyrolysis using a micro-CT system and a high-temperature rock-permeability testing machine. Zhao et al [17] analyzed the pore evolution of Funshun and Yan'an oil shales during pyrolysis with the use of micro-CT. Tiwari et al [10] explored the pore structure and permeability (PABP) of the oil shale before and after pyrolysis using X-ray micro-CT and a lattice Bolzmann simulation; they reported that the patchy porosity was dependent on the distribution of kerogen, and this resulted in incompletely connected flow channels. It is well-known that the apparent anisotropy of oil shale produces different properties.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, Han et al also studied the influence of reaction temperature on the pore structure by conducting the SEM experiment and SEM pictures showed large pore volume and specific surface area of oil shale after heat treatment. Moreover, micro CT was also applied as an efficient approach to quantify the pore structure of oil shale under conventional heating . However, there are limited investigations about the pore structure of oil shale under microwave irradiation, let alone the effects of microwave heating parameters on the pore distribution.…”
Section: Introductionmentioning
confidence: 99%
“…From room temperature to 300 °C, the porosity of oil shale increases slowly, and the porosity dramatically increases at 400 °C. From then on, porosity increases slowly from 500 °C to 600 °C [17,18,20,21], indicating that the main pyrolysis temperature range of oil shale is between 400 °C and 500 °C, as observed by the thermo-gravimetric curve [22]. The decomposition of kerogen in oil shale increases the pressure in the rock, and abundant fissures are produced along the bedding plane of the oil shale, while only a small amount of fractures occur in the direction perpendicular to the bedding plane [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Different from other rocks, oil shale is more sensitive to increases in temperature with regards to its physical and mechanical properties. Under certain temperatures, the organic matter will be pyrolyzed, resulting in the increase of porosity and fracture development [17,18]. The increase of porosity and development of fissures change the low permeability of oil shale under normal temperatures [19].…”
Section: Introductionmentioning
confidence: 99%